Primary clinical care series 2. (Park Lane, Sandown Heinemann Publishers(Pty) Ltd, 2001)
Basic medical sciences, Trauma and emergency, Ear, nose and throat, Skin disease.
Keywords: Primary health care. -- Handbooks, manuals, etc; Clinical medicine -- Handbooks, manuals etc; Preventive medicine -- Handbooks, manuals, etc